(untitled) (Journal of Surgical Sciences, 2020)
Background: Chronic anal fissure is a benign disorder that is associated with considerable discomfort. Surgical treatment in the form of lateral internal sphincterotomy has long been regarded as the gold standard of treatment. Two methods of sphincterotomy are currently practiced: open or closed technique. Objective: The objective of this study was to compare the early outcome of closed versus open lateral internal anal sphincterotomy for the treatment of chronic anal fissure, based on the assessment of post-operative pain and complications. Methods: A comparative study was conducted at the department of surgery in Dhaka Medical College & Hospital, over a period of 6 months from April 2015 to September 2015. A total of 80 patients were purposefully included in this study and were equally divided into two groups; Group A included 40 patients undergone closed lateral internal anal sphincterotomy and Group B included 40 patients undergone open lateral internal anal sphincterotomy. Patients were followed up postoperatively for 6 weeks to assess any complications. The outcomes were compared between the groups using the Chi-square (x2) test and Student’s "t" test. Results: Delayed postoperative healing was found in 7.5% patients of the open lateral internal anal sphincterotomy group. The mean pain score and duration of hospital stay were lower in closed lateral internal anal sphincterotomy group. Conclusion: Closed lateral internal sphincterotomy is preferred to open technique in the treatment of chronic anal fissure, as it is effective, safe, less expensive, and is associated with low complication rate. Journal of Surgical Sciences (2018) Vol. 22 (1): 52-57